2019
DOI: 10.3390/md17070398
|View full text |Cite
|
Sign up to set email alerts
|

New Alkaloids and Polyketides from the Marine Sponge-Derived Fungus Penicillium sp. SCSIO41015

Abstract: The sponge-derived fungus Penicillium sp. SCSIO41015 cultured on solid rice medium yielded twenty-one compounds (1–21), including two new alkaloids (1 and 2) and one new pyrone derivative (3). Their structures were elucidated by analysis of 1D/2D NMR data and HR–ESI–MS. Their absolute configurations were established by single-crystal X-ray diffraction analysis and comparison of the experimental with reported specific rotation values. Compound 16 exhibited selective cytotoxic activity against the human gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Emodin is isolated from different marine-derived fungal species, such as the coral-derived Aspergillus tritici and the sponge-derived Penicillium sp. and Neosartorya fischeri [ 28 , 55 , 56 ]. Marine-derived emodin was tested on different solid cancer models.…”
Section: Anticancer Mechanisms Of Aqs Isolated From Marine Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Emodin is isolated from different marine-derived fungal species, such as the coral-derived Aspergillus tritici and the sponge-derived Penicillium sp. and Neosartorya fischeri [ 28 , 55 , 56 ]. Marine-derived emodin was tested on different solid cancer models.…”
Section: Anticancer Mechanisms Of Aqs Isolated From Marine Fungimentioning
confidence: 99%
“…Marine-derived emodin was tested on different solid cancer models. In gastric MGC803 cancer cells, emodin showed a much stronger cytotoxicity (concentration reducing cell viability by 50% (IC 50 ): 5.19 μM)) [ 56 ] compared to other solid tumors (i.e., ovarian, lung, and hepatocellular), where the IC 50 values were almost 4- to 6-fold higher [ 28 ] ( Table 1 ). However, Tan and colleagues found that in another gastric cell line (SCG7901) emodin 200 μg/mL (740 μM) decreased cell proliferation of only 32.7% after 72 h, thus showing much lesser activity [ 55 ].…”
Section: Anticancer Mechanisms Of Aqs Isolated From Marine Fungimentioning
confidence: 99%
“…All the compounds except quinolactacin E (172) were evaluated for their cytotoxicity versus six human cancer cells as well as their antibacterial behavior against five pathogenic bacteria. None of the tested compounds showed inhibitory potential when examined at concentrations of 5 µM in the preliminary screening [ 48 ]. In addition eight new alkaloids comprising meleagrin B–E (177–180), roquefortine F–I (181–184), and two previously isolated compounds meleagrin (185) as well as roquefortine C (186) were isolated from Penicillium species isolated from deep ocean marine sediment.…”
Section: Classification Of Different Classes Of Alkaloids According To the Diverse Genera Of The Marine-associated Fungi In An Alphabeticmentioning
confidence: 99%
“…In recent years, sponge-derived fungi have drawn increasing attention as a rich source of interesting bioactive marine natural products [1][2][3][4][5][6]. Many fungi associated with marine sponges produce interesting secondary metabolites such as alkaloids, polyketides, and terpenoids [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sponge-derived fungi have drawn increasing attention as a rich source of interesting bioactive marine natural products [1][2][3][4][5][6]. Many fungi associated with marine sponges produce interesting secondary metabolites such as alkaloids, polyketides, and terpenoids [6][7][8][9]. This has encouraged many researchers to explore more bioactive compounds from marine sponge-derived fungi, potentially used as antimicrobials or as anticancer drugs and against other diseases [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%